zad.5 Rozwiąż równanie:
a)3(x-4)-4(2x-7)=2(x+5)
b) 2 (2x-3)+3(4-x)= -(x+1)
c)2(x-3)-4(3+x)=-3(x+2)+2(2x-1)
d)6(x+1)+3(2-x)=2(2x-1)-(4-x)
e) 2(x-7)-3(x+2)=4(x+3)+2 (x-9)
f)-3(x+6)-6(2x+8)= -2(4-x)+9(x+8)
g)-8 (x+2)+3(x+5)=-2(2x+3)+4(2x-1)
h) 6 (4-x)+5(2x-5)=4(x-1)-3(4-x)

3

Odpowiedzi

2010-04-07T17:36:46+02:00
A)3(x-4)-4(2x-7)=2(x+5)
3x-12-8x+28=2x+10
3x-8x-2x=10+12-28
-7x=-6
x=6/7

b) 2 (2x-3)+3(4-x)= -(x+1)
4x-6+12-3x=-x-1
4x-3x+x=-1+6-12
2x=-7
x=-7/2
x=-3,5

c)2(x-3)-4(3+x)=-3(x+2)+2(2x-1)
2x-6-12-4x=-3x-6+4x-2
2x-4x+3x-4x=-6-2+6+12
x=10

d)6(x+1)+3(2-x)=2(2x-1)-(4-x)
6x+6+6-3x=4x-2-4+x
6x-3x-4x-x=-2-4-6-6
-2x=-18
x=9

e) 2(x-7)-3(x+2)=4(x+3)+2 (x-9)
2x-14-3x-6=4x+12+2x-18
2x-3x-4x-2x=12-18+14+6
-7x=14
x=-2

f)-3(x+6)-6(2x+8)= -2(4-x)+9(x+8)
-3x-18-12x-48=-8+2x+9x+72
-3x-12x-2x-9x=-8+72+18+48
-26x=130
x=-5

g)-8 (x+2)+3(x+5)=-2(2x+3)+4(2x-1)
-8x-16+3x+15=-4x-6+8x-4
-8x+3x+4x-8x=-6-4+16-15
-9x=-9
x=1

h) 6 (4-x)+5(2x-5)=4(x-1)-3(4-x)
24-6x+10x-25=4x-4-12+3x
-6x+10x-4x-3x=-4-12-24+25
-3x=-15
x=5
Najlepsza Odpowiedź!
2010-04-07T17:38:32+02:00
A)
3(x-4)-4(2x-7)=2(x+5)
3x-12-8x+28=2x+10
3x-2x-8x=12-28-10
-7x=-26
7x=26/:7
x=²⁶/₇
x=7⁵/₇
b)
2 (2x-3)+3(4-x)= -(x+1)
4x-6+12-3x=-x-1
4x-3x+x=6-12-1
2x=7/:2
x=3½
c)
2(x-3)-4(3+x)=-3(x+2)+2(2x-1)
2x-6-12-4x=-3x-6+4x-2
2x-4x+3x-4x=6+12-6-2
-3x=10
3x=-10/:3
x=3⅓
d)
6(x+1)+3(2-x)=2(2x-1)-(4-x)
6x+6+6-3x=4x-2-4+x
6x-3x-4x-x=-6-6-2-4
-2x=-18
2x=18/:2
x=9
e)
2(x-7)-3(x+2)=4(x+3)+2 (x-9)
2x-14-3x-6=4x+12+2x-18
2x-3x-4x-2x=14+6+12-18
-7x=14
7x=-14/:2
x=-2
2010-04-07T17:38:53+02:00
A)3(x-4)-4(2x-7)=2(x+5)
3x-12-8x+28=2x+10
-7x=-6
x= 6/7

b) 2 (2x-3)+3(4-x)= -(x+1)
4x-6+12-3x=-x-1
2x=-7
x= -3,5

c)2(x-3)-4(3+x)=-3(x+2)+2(2x-1)
2x-6-12-4x=-3x-6+4x-2
-3x=10
x= -3 i 1/3

d)6(x+1)+3(2-x)=2(2x-1)-(4-x)
6x+6+6-3x=4x-2-4+x
-2x=-18
x=9

e) 2(x-7)-3(x+2)=4(x+3)+2 (x-9)
2x-14-3x-6=4x+12+2x-18
-7x=14
x=-2

f)-3(x+6)-6(2x+8)= -2(4-x)+9(x+8)
-3x-18-12x-48=-8+2x+9x+72
-26x=130
x=-5

g)-8 (x+2)+3(x+5)=-2(2x+3)+4(2x-1)
-8x-16+3x+15=-4x-6+8x-4
-9x=-9
x= 1

h) 6 (4-x)+5(2x-5)=4(x-1)-3(4-x)
24-6x+10x-25=4x-4-12+3x
-3x=-15
x=5